UTILIZATION OF MARITIME WEATHER INFORMATION FOR SHIPPING SAFETY IN ACEH - Syindi Airikvita; Muliadi Sembiring; Thaib Rizwan; Ichsan Setiawan; Syarifah Meurah Yuni (Jurnal Pengabdian Bangsa, 2026)
This community service project is entitled "Utilization of Maritime Weather Information for Shipping Safety in Aceh Province." This community service will last for one month, namely August 2023, at the Class 1 Sultan Iskandar Muda Meteorological Station BMKG office, Cot Mancang, Kuta Baro District, Aceh Besar Regency. High waves can occur due to several factors. According to the National Oceanic and Atmospheric Administration website and various other sources, these factors include strong winds, distance and travel time of the wind, differences in temperature and air pressure, interactions between waves, complex ocean currents, and underwater earthquakes. Many factors support the smooth and safe sailing of ships at sea. One of them is natural factors or weather conditions that will significantly influence shipping activities in Indonesia. Therefore, information about weather forecasts is very important in shipping activities. The purpose of this community service is to understand the importance of maritime weather information for shipping and fishermen to facilitate their activities. High waves are more common in the waters north of Sabang, the northern part of the Strait of Malacca, the waters west of Aceh, the Indian Ocean west of Aceh, and the surrounding areas. These areas frequently experience high waves because they are located in open seas, which are more prone to high waves. The waters between Sabang and Banda Aceh still have low to moderate wave heights.